Challenges and Barriers in Patient Reporting of Adverse Effects from Over-the-Counter (OTC) Drugs: A Narrative Review - Utami, Fella Arifatul Wahyu; Gunawan A Sumule, Joshua; Suryani Pangaribuan, Ika (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Over-the-counter (OTC) drugs are commonly used for self-medication because of their availability and perceived safety. However, adverse drug reactions (ADRs) associated with OTC drugs are frequently underreported, posing significant risks to public health. This narrative review aims to identify the main challenges and barriers that prevent patients from reporting adverse effects of OTC drug use. Literature was retrieved from PubMed, ScienceDirect, Google Scholar, and national journals, focusing on publications from 2019 to 2024. The review reveals three major barriers: (1) limited knowledge and misconceptions about OTC drug safety, (2) socio-cultural influences such as stigma and reliance on traditional medicine, and (3) systemic obstacles including complicated reporting procedures and insufficient involvement of healthcare providers. Collectively, these barriers reduce the effectiveness of pharmacovigilance systems. This review underscores the urgent need for patient education, stronger pharmacist engagement, and the integration of digital pharmacovigilance platforms to ensure safe and responsible use of OTC drugs.